STATUS ZINC DAN PERAN SUPLEMENTASI ZINC TERHADAP SISTEM IMUN PADA PASIEN HIV/AIDS: A SYSTEMATIC REVIEW [Zinc Status and The Role of Zinc Supplementation on Immune System in HIV/AIDS Patients: A Systematic Review] - Putri Hersya Maulia; Farapti Farapti (Universitas Airlangga, 2019)
Zinc has a potential role in defense system by taking control in immunity cells activity. Zinc is a micro-nutrient that attains in such prominence as a co-factor for hundred enzymes and inducing nutritional metabolism. In condition of HIV infection, low plasma zinc level can inhibit T cell establishment, then decreasing humoral and cellular immunity. Furthermore, zinc plasma defi ciency will impact the disease progression thus increasing mortality rate. Based on several studies, giving zinc supplementation to HIV/AIDS patient still shows controversial results. The aim of this systematic review was to analyze zinc status in HIV/AIDS patients and examine the effect of zinc supplementation related to immunity status. The method of the study was conducted comprehensive searches on adults HIV infected aged >18 years who underwent outpatient care or hospitalized that received single zinc supplementation or in multivitamin and minerals form. The result from nine studies demonstrated that most of HIV/AIDS patients have a low plasma zinc level and after receiving zinc supplementation with a dose at least 12 mg for more than 1 month consecutively, the lymphocytes CD4+ and IFN-γ status in HIV/AIDS patients was increasing. Furthermore, the intervention of zinc supplementation also showed some positive improvement in other infections occurrence such as diarrhea, pneumonia, and tuberculosis. Zinc supplementation on HIV/AIDS patient has many benefi ts in increasing zinc status and improving the immune system.